CORRELATION BETWEEN DURATION SPENT IN FITNESS CENTER AND VO2 MAX LEVEL AMONG ADULTS - Mohammad Sabiq; Putri HA Rahman; Kurnia Wahyudi (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
VO2 max or oxygen consumption maximum value is a gold standard indicator towards cardiovascular and aerobic endurance because it refers to the maximum amount of oxygen used by an individual in one minute during maximum physical activity. The study's purpose was to see the correlation between duration spent in the fitness center and VO2 max value among adults. This study used the analytical study method, cross-sectional type. We chose the participant from members of Gold’s Gym fitness center at Cihampelas, aged 18-45 years old, with 3 months minimum of activity, and exercise frequency around three times per week. Theparticipants who had cardiovascular and pulmonary disease, serious physical injury, had already exercised during the time of observation, or professionally trained athletes were excluded. We used the Queen College step test for the instrument. There were 47 participants in this study. Spearman’s correlation coefficient was calculated to measure the correlation between duration spent and VO2 max, and the result was 0.77(95% CI 0.64; 0.85), p<0.001 which is categorized as a strong correlation. From this study, we found that with the increase of duration spent in the fitness center, the VO2 max level is also increasing, and vice versa. This result is supported by a study from the United States which finds a correlation between VO2max and performance times of recreational triathletes. In conclusion, there is a positive correlation between duration spent in the fitness center and VO2 max level among adults.